The Development of Local Accommodation to Support Subak Jatiluwih Tourism in Tabanan Regency - Muriawan Putra, Agus; Astina, Ida Bagus Ketut (Udayana Journal of Social Sciences and Humanities, 2017)
The aim of research to develop local accommodations Jatiluwih, so tourists can stay longer in Jatiluwih and the community direct can interacts with tourists and direct benefit also from the tourists who stay. In this research, using qualitative descriptive analysis and the determination of sampling is quota sampling method and method of sampling taking with Slovin method. This research took place in JatiluwihVillage, Penebel District, Tabanan Regency. Key research findings show that there are still many obstacles the development of local Jatiluwih accommodations, such as: human resources, supporting facilities, the presence of the Holy Place, a large family does not agree, and promotions. In addition, in the development of local Jatiluwih accommodations there are several criteria that must be filled according the community, such as: obey with the rules in the village, not allowed in the Holy Place, keep hygiene, improved facilities, the easy of working capital, the coaching routine of related parties and criteria according tourists, such as: hospitality, cleanliness and security, mastery of English, supporting facilities, the willingness to interact with tourists, and the easy of information. Also, some programs in the development of local Jatiluwih accommodations, such as: dissemination to the public, collect data on houses to be used as a local accomodations, training, funding, establish a local accommodations management, preparing tourism package and tourism product of Jatiluwih, and promotions.